COMBINED ANESTHESIA IN SIMULTANEOUS OPERATIONS OF GALLBLADDER AND SMALL INTESTINE - Qurbonov Navruzbek Zayniddinovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The consideration of reliable means of anesthesia when performing one-stage operations on the abdominal and pelvic organs is one of the most important links in the treatment of surgical patients. Study of surgical stress severity, regional anesthesia method application, hypnotic component, influence of artificial lung ventilation, anesthesia in surgery, general anesthesia, and opioids on cognitive and psychomotor functions; provision of positive effect when epidural anesthesia is used in combination with general anesthesia.